Culturally Responsive Teaching to Support Meaningful Learning in Mathematics Primary School: A Content Analysis in Student's Textbook - Murti, Rahayu Condro (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
This study aims to measure and determine, through analysis, the textbooks used by elementary school students, especially in mathematics. The analysis seeks to examine how the aspects of culturally responsive teaching (CRT) in the textbook supports meaningful learning and supports the aspects of